2013
DOI: 10.1111/evo.12135
|View full text |Cite
|
Sign up to set email alerts
|

SEXUAL TRAITS ARE SENSITIVE TO GENETIC STRESS AND PREDICT EXTINCTION RISK IN THE STALK‐EYED FLY,DIASEMOPSIS MEIGENII

Abstract: The handicap principle predicts that sexual traits are more susceptible to inbreeding depression than nonsexual traits. However, this hypothesis has received little testing and results are inconsistent. We used 11 generations of full-sibling mating to test the effect of inbreeding on sexual and nonsexual traits in the stalk-eyed fly Diasemopsis meigenii. Consistent with the theoretical predictions, the male sexual trait (eyespan) decreased more than nonsexual traits (female eyespan and male wing length), even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…Morphological data across a wide range of taxa generally corroborate these predictions (e.g. birds: [34,35]; flies: [30,36]; beetles: [37]; fish: [38]; crustaceans: [39]), and at least one study on fruit flies has been able to demonstrated that high-condition populations are more sexually dimorphic in transcription than low-condition populations [40]. However, more precise knowledge of the transcriptomic underpinnings of condition-dependence is lacking [24].…”
Section: Introductionmentioning
confidence: 96%
“…Morphological data across a wide range of taxa generally corroborate these predictions (e.g. birds: [34,35]; flies: [30,36]; beetles: [37]; fish: [38]; crustaceans: [39]), and at least one study on fruit flies has been able to demonstrated that high-condition populations are more sexually dimorphic in transcription than low-condition populations [40]. However, more precise knowledge of the transcriptomic underpinnings of condition-dependence is lacking [24].…”
Section: Introductionmentioning
confidence: 96%
“…Eyespan is sexually dimorphic, with males having more widely displaced eyes than females (Baker and Wilkinson 2001) and is subject to sexual selection through female choice for large male ornamentation (Burkhardt and de la Motte 1988; Wilkinson et al 1998; Cotton et al 2006). Male eyespan is a highly condition-dependent trait in D. meigenii (Bellamy et al 2013) and other stalk-eyed fly species (David et al 1998; Bjorksten et al 2001; Cotton et al 2004). In the related stalk-eyed fly species Teleopsis dalmanni , eyespan is a reliable indicator of the size of male internal reproductive organs (Rogers et al 2008; Cotton et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A suite of 105 inbred lines were founded from a stock of Diasemopsis meigenii (Bellamy et al, ), an African stalk‐eyed fly, derived from flies collected in South Africa by S. Hilger in 2000. After 11 generations of full‐sib mating ( f ~ 0.908), the extant lines were bred in cage culture (~200 flies/cage).…”
Section: Methodsmentioning
confidence: 99%
“…Eggs were collected from each line, and larvae were raised on excess puréed sweet corn. At eclosion, offspring were placed in large cages, separated by sex (~2 weeks), raised until sexual maturity (~10 weeks) and kept under standard conditions (Bellamy et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation